Assessment of promising agricultural management practices - Barão, L. (2020)
iSQAPER project - Interactive Soil Quality Assessment in Europe and China for Agricultural Productivity and Environmental Resilience - aims to develop an app to advise farmers on selecting the best Agriculture Management Practice (AMPs) to improve soil quality. For this purpose, a soil quality index has to be developed to account for the changes in soil quality as impacted by the implementation of the AMPs. Some promising AMPs have been suggested over the time to prevent soil degradation. These practices have been randomly adopted by farmers but which practices are most used by farmers and where they are mostly adopted remains unclear. This study is part of the iSQAPER project with the speciﬁc aims: 1) map the current distribution of previously selected 18 promising AMPs in several pedo-climatic regions and farming systems located in ten and four study site areas (SSA) along Europe and China, respectively; and 2) identify the soil threats occurring in those areas. In each SSA, farmers using promising AMP's were identiﬁed and questionnaires were used to assess farmer's perception on soil threats signiﬁcance in the area. 138 plots/farms using 18 promising AMPs, were identiﬁed in Europe (112) and China (26).Results show that promising AMPs used in Europe are Crop rotation (15%), Manuring & Composting (15%) and Min-till (14%), whereas in China are Manuring & Composting (18%), Residue maintenance(18%) and Integrated pest and disease management (12%). In Europe, soil erosion is the main threat in agricultural Mediterranean areas while soilborne pests and diseases is more frequent in the SSAs from France and The Netherlands. In China, soil erosion, SOM decline, compaction and poor soil structure are among the most signiﬁcant. This work provides important information for policy makers and the development of strategies to support and promote agricultural management practices with beneﬁts for soil quality.